PENERAPAN TEYENGAN LIMBAH BESI PADA KAIN PRIMA DALAM PEMBUATAN KEMEJA PRIA MODIFIKASI - Atiqoh Atiqoh (SNHRP, 2021)
Contemporer batik is a type of batik that is not bound by ancient rules and develops to the present era which is made by using modern motifs, made from rusty iron waste which be used as a teyeng stain motif which will be applied to modified men's shirts. This study aims to explain the process of making prime fabrics which will later be processed into batik cloth with iron waste teyengan motif and will be applied to modified men's shirts. Knowing the finished results and the interest in the response from young men to modified men's shirts using iron waste in prime fabrics. This research method uses a quantitative approach using experimental methods. Data collection techniques were observation, documentation and questionnaires to determine the finished result and interest in modified men's shirts using iron waste. The result of making this iron waste utilization motif requires a long process in its manufacture, because each iron waste material used will not be 100% the same as the iron waste material applied to the prime cloth. After seeing the respondent's opinion, it can be concluded that the making of men's shirts using iron waste in prime fabrics is more desirable because it can be seen from the motifs that have never existed and the models of these combinations of combinations are in demand by young men. The suggestion in making batik using iron waste is that it should not only be applied to men's clothing but also women's clothing.